(untitled) (Scientific journal of the Fergana State University, 2024)
Although a number of George Eliot’s novels deal with the fate of the nation and the way of life of the English people and are heavily criticised, "Daniel Deronda" is the most critical novel, embodying the differences in Victorian life, English rhetoric, religious and cultural life, prejudice, law and law uniting national myths, stratification and class death. In addition, Daniel Deronda, considered to be George Eliot’s most didactic novel, although the author criticises English society at the same time, makes the reader gain a sense of identity, values and self-respect. This article aims to more fully reveal to the readers about the novel Daniel Deronda, which is considered the last novel by George Eliot, and the nature of character, drawing upon definitions and attitudes to that term. It looks at how certain of Eliot’s characters are formed, considering them in their varying levels of success as representations of people, and how they have been received by critics over time.